Assessment of limb edema in pediatric post‐thrombotic syndrome. Issue 3 (17th April 2018) - Avila, Maria L.; Feldman, Brian M.; Williams, Suzan; Ward, Leigh C.; Montoya, Madeline I.; Stinson, Jennifer; Kiss, Alex; Vincelli, Jennifer; Lumia, Celeste; Brandão, Leonardo R.
Abstract: Background: Pediatric tools for diagnosis of post‐thrombotic syndrome (PTS) include the assessment of limb edema as a symptom (patient/proxy‐reported) and as a sign. However, it is unclear whether these two approaches refer to the same clinical aspect of PTS. This could result in overestimation of disease severity. We sought to evaluate the correlation among different techniques to assess limb edema as a sign and as a symptom in children who sustained upper extremity (UE) or lower extremity (LE) deep vein thrombosis (DVT) and were, therefore, at risk of PTS. Methods: Limb edema was cross‐sectionally measured as a symptom (ie, patient‐ or proxy‐reported) and as a sign (ie, clinician‐assessed limb circumference difference, limb volume ratio, bioimpedance spectroscopy ratio (BIS), and durometry ratio) in 140 children at risk of PTS (n = 70 UE‐DVT, n = 70 LE‐DVT). Item‐item correlations were estimated using Pearson or Spearman correlation coefficients, as appropriate, and separately for the UE and LE groups. Results: In the UE‐DVT group, proxy‐reported swelling correlated weakly to moderately with circumference difference and with volume ratio, but not with BIS ratio. In the LE‐DVT group, proxy‐reported swelling correlated moderately with thigh circumference difference and volume ratio, and patient‐reported swelling correlated moderately with BIS ratio. Conclusion: Our findings suggest that patient/proxy‐reported and clinician‐assessed limb edema measure slightly different aspects of PTS, justifying their inclusion in pediatric PTS tools. In addition, proxy‐reported swelling was in closer agreement with clinician‐assessed total limb size (ie, observed edema), and patient‐reported swelling in the LE seemed to reflect limb fluid content (ie, perceived edema).